The burden of prostate cancer in the North Africa and Middle East Region from 1990 to 2021 - Saeid Safiri; Ali Shamekh; Kamaleddin Hassanzadeh; Asra Fazlollahi; Mark J. M. Sullman; Mortaza Raeisi; Ali-Asghar Kolahi (Scientific Reports, 2025)
Abstract Prostate cancer ranks among the most prevalent malignancies affecting males globally. This study sought to document the incidence, deaths and disability-adjusted life-years (DALYs) that were due to prostate cancer in the Middle East and North Africa (MENA) region, and its 21 countries, from 1990 to 2021. We analysed publicly accessible data from the Global Burden of Disease 2021 study to present findings on the incidence, deaths, and disability-adjusted life years (DALYs) associated with prostate cancer. These metrics were reported as counts and age-standardised rates, each accompanied by 95% uncertainty intervals. In 2021, the age-standardised incidence of prostate cancer in the region was 27.4 per 100,000 population, representing a 125.1% increase from 1990. The age-standardised mortality rate was 10.1, and the age-standardised DALY rate was 173.6, neither of which showed significant increases since 1990. Qatar recorded the highest age-standardised DALY rate in 2021, while Algeria had the lowest. The largest number of incident cases, deaths, and DALYs in 2021 were found in the 65–69, 80–84, and 70–74 age groups, respectively. Additionally, from 1990 to 2021, the burden of prostate cancer largely increased with the socio-demographic index (SDI) at the regional level. The burden of prostate cancer in the MENA region rose markedly between 1990 and 2021. Further studies into the underlying causes of this increasing incidence are essential to devise effective strategies for the early detection and prevention of the disease.